Qadliyah al-Dalalah fi ‘Ilm al-Tarbiyah al-Islamiyyah - Fitri Zakiyah (Jurnal Alsinatuna, 2018)
This paper aims to discuss about semantic issue related to terms often used in Islamic education context, namely ta’lim, tarbiyah, ta’dib and tadris. The study shows that ta’lim and tarbiyah have a broader meaning and most commonly used in educational institutions. Term ta’dibhave more specific meaning and interpret the main goal of education in philosophy of Islamic education. While term tadris basicly more emphasis on the active role of students in learning and teaching process. These terms have different dimension of meaning but interconnected each other. There is no contradiction of meaning of them because there is the same basic goal of production of meaning from these words. The proper understanding of these meaning is important and need to be considered in preparing the design of learning in order to the process of learning run effectively and achieve the targetted goal.